Sheep CD34+ Amniotic Fluid Cells Have Hematopoietic Potential and Engraft After Autologous In Utero Transplantation. (January 2015) - Shaw, S. W. Steven; Blundell, Michael P.; Pipino, Caterina; Shangaris, Panicos; Maghsoudlou, Panagiotis; Ramachandra, Durrgah L.; Georgiades, Fanos; Boyd, Michael; Thrasher, Adrian J.; Porada, Christopher D.; Almeida‐Porada, Graça; Cheng, Po‐Jen; et al.
Abstract Unmatched allogeneic in utero stem cell transplantation (IUSCT) produces poor engraftment unless the fetus has congenital immunodeficiency, probably because of maternal and fetal immune responses to injected cells. We studied the functional hematopoietic potential of transduced green fluorescent protein (GFP+) sheep amniotic fluid (AF) stem cells, before and after autologous IUSCT. CD34+ cells were selected from first trimester sheep AF, transduced overnight, and injected intravenously into NOD‐SCID‐gamma (NSG) mice. At 3 months, primary recipient bone marrow (BM) was injected into secondary NSG recipients. GFP+ cells were detected in the hematopoietic organs and peripheral blood of primary and secondary recipients at 3 months. Autologous IUSCT (transduced GFP+CD34+AF) was performed in fetal sheep. Six months postnatally, lamb BM was injected into secondary NSG recipients. GFP+ cells were detected in the peripheral blood of primary and secondary recipients. This confirms the hematopoietic potential of AF stem cells supporting the concept of autologous IUSCT to treat congenital hematopoietic disease. Stem Cells2015;33:122–132